Potencial e lacuna de produtividade em arroz irrigado na Argentina e fatores de manejo que afetam a produtividade - Meus, Lorenzo Dalcin (2021)
Due to the over concentration of the rice production in Asia, the study and comprehension of rice producing chains outside this continent are key do guarantee the global food security. The objective of this work was quantify the Yield potential (Yp), and Yield gap (Yg) of irrigated rice in Argentina; identify the main management practices that explain the gaps; identify that current yield plateau in Argentina is being caused by the ceiling of the Yp or it can be reverted by increasing the yield trough adjusting management practices; and validating the SimulArroz and ORYZA models to Argentina. The study was done by analyzing field data from more than 2,700 field across 10 growing seasons, and by estimations with the crop simulation model SimulArroz and ORYZA v3. The average irrigated rice yield potential for subtropical Argentina estimated by the SimulArroz model ranged from 3.8 to 15.6 Mg ha−¹, and from 7.6 to 14.3 Mg ha−¹ in the ORYZA v3. Yp was higher in Southern (15.1 Mg ha−¹) and lower in Northern (13.4 Mg ha−¹), and the highest values of Yp were found in the sowing dates of September and October. The Yg in Argentina is 53% of the Yp, ranging from 47 to 56% across regions. The main management factors affecting farmers yield is absence of crop rotation, sowing dates and irrigation. The increase in the rice production in Argentina if the fields close the exploitable gap would be 916,091 tons of rice annually, or an increase of 42% in the Argentina rice production without increase the sowed area. The yield plateau in rice production in Argentina can be changed by adopting management practices that increase the average grain yield. There is room to increase the average rice yield in Argentina by closing the yield gap.